Metastasis tumour suppressor-1 and the aggressiveness of prostate cancer cells - MUSTAFA, NOHA (D.A. Spandidos, 2011)
Previous studies have suggested that metastasis tumour suppressor-1 (MTSS1) plays a key role in cancer metastasis. Firstly, in this study we assessed MTSS1 expression levels in prostate cancer cell lines to reveal any changes in cell properties. Secondly, we aimed to clarify the cellular function of MTSS1 in prostate cancer cells. MTSS1 expression levels were assessed in different types of cancer cell lines through the RT-PCR analysis technique. The influence of MTSS1 was further examined via biological overexpression and knockdown in the prostate cancer cell lines. Two prostate cell lines were chosen for either knockdown or overexpression of the MTSS1 gene. The overexpression of MTSS1 in PC-3 human prostate cancer cells significantly suppressed the migratory, growth and adherence properties of the cells (p<0.01). By contrast, the knockdown of MTSS1 in DU-145 human prostate cancer cells dramatically enhanced these properties (p<0.001). We concluded that MTSS1 demonstrates the ability to play a role in controlling the metastatic nature of prostate cancer cells.